The Influence of The Early Warning Health Strategies and Decisions at Intensive Care Unit - Patriana, Dhona; Girsang, Ermi; Nasution, Ali N. (Poltekkes Kemenkes Tanjung Karang, 2025)
In the era of BPJS Kesehatan (national health insurance), business competition among hospitals is intensifying, with hospitals striving to offer unique and excellent services while upholding the principles of healthcare ethics. Hospitals can optimize the existing infrastructure and tools to outperform their competitors. This study aims to determine the effect of the 7P marketing mix strategy (product, price, place, promotion, people, process, and physical evidence) on patient loyalty. This study is a quantitative analytic study with a cross-sectional design conducted at Royal Prima Medan Hospital (RPMH). This study enrolled 398 outpatients who completed valid and reliable questionnaires using an online application. Data were analyzed using binomial logistic regression tests to determine the factors most influencing patient loyalty. The Prima Indonesia University Health Research Ethics Committee has ethically cleared this study. This study found that over 70% of respondents had a good perspective on all aspects of the health decision for early warning, and RPMH successfully activated 73.12% of decisions. Bivariate analysis showed that all aspects of the 7P marketing mix were associated with patient loyalty (p<0.001). The study concluded that the 7P marketing mix strategy has a significant and positive influence on patient loyalty, with the most influential factor being people or human resources (p < 0.001; OR: 33.628). It is highly recommended that hospitals emphasize training in their human resources to nurture patient loyalty to the hospital.